SOCIETY INTERESTS, PROFESSIONAL COMPETENCE AND ETHICAL REQUIREMENTS FOR PROFESSIONAL ACCOUNTANTS - Khamidullina Zuleikha Chulpanovna; Yusupova Malika Botiraliyevna; Mamazhonov Akramjon Turgunovich (Scholar Express Journals, 2021)
Recognizing the growing responsibility of the accounting profession to society, the authors in the article try to prove the necessity and importance of the principles established by the Code of Ethics for Professional Accountants, and also reveals the essence of the fundamental principles of professional conduct of accountants
Keywords: Code of Ethics; the profession of an accountant; fundamental principles; decency